The Violence of Political Empowerment: Electoral Success and the Facilitation of Terrorism in the Republic of India. Issue 7 (3rd October 2022) - Dmello, Jared R.; Perliger, Arie; Sweeney, Matthew
ABSTRACT: Ideological violence, according to previous research, tends to spike following what may be perceived as an electoral success of an ideologically-affiliated political camp. Despite a growing number of examples across the globe, the extent to which ideological success in electoral processes impacts terrorism within constituencies remains under-researched. This exploratory analysis seeks to examine how majority-minority outcomes in the electoral process influence terrorism in democratic states. This study employs a longitudinal case study approach for the Republic of India, using publicly available data from the Census of India and open-sourced data on terrorist activity. We find that economic stress most strongly impacts the likelihood that supporters of the political majority will engage in terrorist activity, followed by social cohesion, measured through religious homogeneity.